Fakultas Ushuluddin dan Penguatan Kearifan Lokal untuk Membangun Karakter Bangsa - F a u z i F a u z i (Ar-Raniry: International Journal of Islamic Studies, 2014)
Local wisdom is the precious heritage in building a dignified society. Therefore, it should be explored and promoted in human life. This agenda must necessarily be carried out by an institution that has sufficient capability and capacity. Faculty as the heart of the nation with its human resources should have been involved in the processing of thinking out the wisdom. The involvement would be done gradually and continuously from planning to transfer to the users (community) with the appropriate and accurate approaches. Revitalization and re-actualization, the transformation of culture, cultural development priorities, and the development of wisdom values-based character building through development, to be a step of local wisdom re-actualization should be part of the theology faculty activity.